UJI AKTIVITAS ANTIBAKTERI EKSTRAK AIR DAN ETANOL UMBI BAWANG DAYAK (Eleutherine palmifolia (L.) Merr) TERHADAP BAKTERI PENYEBAB INFEKSI SALURAN PENCERNAAN - Rusli, Rusli; Nurung, Ayyub Harly; Erwing, Erwing; Massaressung, Andi (As-Syifaa Jurnal Farmasi, 2024)
Umbi bawang dayak (Eleutherine palmifolia (L.) Merr) is a traditional medicinal plant that has been used empirically to treat dysentery, stomach pain, and cancer. This plant has antimicrobial properties and contains naphthoquinone, alkaloids, flavonoids, saponins, tannins, and steroids. This study aims to assess the antibacterial effectiveness of water and ethanol extracts of umbi bawang dayak against E. coli, S. thypi, V. cholerae, and S. dysentriae. Minimum Inhibitory Concentration and Minimum Bactericidal Concentration values using the agar diffusion method with concentrations ranging from 25.6%, to 0.025% and its bioautgram profile, indicated notable antibacterial activity from both extracts. The MIC and MBC values for the aqueous extract against E. coli, S. thypi, and V. cholerae were at 1.6% concentration, while for S. dysentriae, at 0.8% concentration. The ethanol extract showed MIC values of 1.6% for E. coli, S. thypi, and V. cholerae, with 0.8% for S. dysentriae while MBC was 1.6% against all test bacteria. KLT-Bioautography analysis using n-hexane 4:1 ethyl acetate eluent revealed distinct compound profiles in both extracts, confirming efficient inhibition against the evaluated bacteria. Furthermore, while E. coli, S. thypi, and V. cholerae evidenced consistent MIC values in both extracts, S. dysentriae showcased ethanol extract superior MBC efficacy at 0.8% versus the water extract at 1.6%. Moreover, the ethanol extract demonstrated a richer compound composition with six active spots compared to the three spots apparent in the aqueous extract of umbi bawang dayak (Eleutherine palmifolia (L.) Merr).